Trading Tasks: A Dynamic Theory of Offshoring - Sebastian Benz (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
This paper is a dynamic extension of the well-known theory of trade in tasks by Grossman & Rossi-Hansberg (2008). In my model, a firms offshoring decision is governed by production cost savings, but also considers potential imitation risk. I show that such a consideration reduces the level of offshoring compared to a static optimization and that adjustment of offshoring volume with respect to changes in offshoring costs or labor endowment is characterized by overshooting and subsequent movement toward a steady state. Moreover, I find that offshoring affects wages via more channels than are apparent in static models. More precisely, I identify a shortrun intertemporal profit effect and a long-run composition effect, both of which depend on the endogenous rate of product imitation. These effects can reverse wellknown static wage effects from offshoring, such as the labor supply effect and productivity effect. The dynamic adjustment predicted by this model has important implications on empirical strategies to identify a meaningful correlation of offshoring and relative wages.
Keywords: F12; F16; F43; J31; O34; 330; Offshoring; trade in tasks; skill premium; imitation